The apple DNA-binding one zinc-finger protein MdDof54 promotes drought resistance. (1st December 2020) - Chen, Pengxiang; Yan, Mingjia; Li, Lei; He, Jieqiang; Zhou, Shuangxi; Li, Zhongxing; Niu, Chundong; Bao, Chana; Zhi, Fang; Ma, Fengwang; Guan, Qingmei
Abstract: DNA-binding one zinc-finger (Dof) proteins constitute a family of transcription factors with a highly conserved Dof domain that contains a C2C2 zinc-finger motif. Although several studies have demonstrated that Dof proteins are involved in multiple plant processes, including development and stress resistance, the functions of these proteins in drought stress resistance are largely unknown. Here, we report the identification of the MdDof54 gene from apple and document its positive roles in apple drought resistance. After long-term drought stress, compared with nontransgenic plants, MdDof54 RNAi plants had significantly shorter heights and weaker root systems; the transgenic plants also had lower shoot and root hydraulic conductivity, as well as lower photosynthesis rates. By contrast, compared with nontransgenic plants, MdDof54 -overexpressing plants had higher photosynthesis rates and shoot hydraulic conductivity under long-term drought stress. Moreover, compared with nontransgenic plants, MdDof54 -overexpressing plants had higher survival percentages under short-term drought stress, whereas MdDof54 RNAi plants had lower survival percentages. MdDof54 RNAi plants showed significant downregulation of 99 genes and significant upregulation of 992 genes in response to drought, and 366 of these genes were responsive to drought. We used DAP-seq and ChIP-seq analyses to demonstrate that MdDof54 recognizes cis -elements that contain an AAAG motif. Taken together, our results provide new information on the functions of MdDof54 in plant drought stress resistance as well as resources for apple breeding aimed at the improvement of drought resistance.